Évolution et perspectives de l’assurance-vie - Poitras, Jean-Marie (Assurances, 1983)
This is the text of the speech of Mr. Jean-Marie Poitras to the members of the Quebec Association of Fiscal and Estate Planning, on October 7th 1982. Mr. Poitras discusses certain problems caused by the present state of life insurance in Canada. His conclusion: “The state should leave more room for free enterprise, relying on individuals’ dedication and sense of responsibility.”